Research Project as a Tool for Teaching Text Analysis Methods: Predicting the Post Class in the Social Network - Суворова, Алена Владимировна; Смирнова, Карина Руслановна; Будин, Евгений Александрович; Тулупьева, Татьяна Валентиновна; Тулупьев, Александр Львович; Абрамов, Максим Викторович (Computer Tools in Education, 2018)
The article describes a student research project on predicting the class of a post on a social network based on its textual content. The features of the project are discussed as an integral part of the trajectory of teaching data analysis methods, including text analysis methods and tools that are often not included in machine learning courses. The formulation of the problem, the stages of its solution, the sequence of considering new methods as a way for solving students’ problems, as well as the used tool of the R environment are described. The possibilities of expanding the task and its modifications depending on the level of training of students are given.